The Phenomenon of Personal Data as a “Pseudo Guarantee” In Fintech: Legal or Not? - Uswatun Hasanah; Djulaeka, Djulaeka; Murni, Murni; A. Zaenurrosyid (JUSTISI, 2025)
The study aims to examine the validity of personal data as a "pseudo guarantee" in fintech lending. The focus of this problem is whether the phenomenon of using personal data as a debt guarantee is justified. The research method is normative, employing a statute, a conceptual and a historical approach. The analysis uses deductive logic and teleological interpretation. Novelty of this study is different from offline loan agreements that are based on collateral, fintech is not based on collateral, but personal data has a dual function, first as the main basis for determining whether or not credit is approved and second as a pseudo guarantee if the debtor defaults. The results show that personal data is the basis of the platform to collect and "execute loans" by disseminating personal data of loan recipients to the contact numbers of people close to the borrower if the debtor defaults. The PDP Law, POJK No. 10/POJK.05/2022 and POJK No. 22 of 2023 prohibit Fintech from providing consumer data to other parties. Fintech organizers are required to keep the confidentiality of borrower data in accordance with the data acquisition agreement with the data owner. Conclusion, the use of personal data as a "pseudo guarantee" by providing consumer data to other parties if the loan recipient fails, based on POJK No. 10/POJK.05/2022 and Law No. 19 of 2016 is permitted as long as prior written consent is obtained from the owner of the personal data.